2009
DOI: 10.1061/(asce)0899-1561(2009)21:11(666)
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure Changes of Blended Cement Pastes Containing Fly Ash, Rice Husk Ash, and Palm Oil Fuel Ash Caused by Carbonation

Abstract: In this paper, the effects of carbonation on pore structure of blended pozzolan cement pastes were investigated. Ordinary Portland cement ͑OPC͒ was partially replaced with ground palm oil fuel ash ͑POA͒, ground rice husk ash ͑RHA͒ and classified fine fly ash ͑FA͒. The strength, total porosity, specific surface area, and pore size distribution were tested. In general, incorporation of pozzolans increased the total porosity of blended cement pastes in comparison to that of OPC paste. Carbonation of pastes under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 21 publications
(7 reference statements)
4
20
0
1
Order By: Relevance
“…This is because fine particles size of FA improves the packing effect of coarse POFA hence produced a denser blended concrete. This statement was also supported by Isaia et al, [10] and Rukzon et al, [23]. They stated that incorporation of fine pozzolans in blended concrete improves the strength of concrete due to synergic effects.…”
Section: Slump Testsupporting
confidence: 65%
“…This is because fine particles size of FA improves the packing effect of coarse POFA hence produced a denser blended concrete. This statement was also supported by Isaia et al, [10] and Rukzon et al, [23]. They stated that incorporation of fine pozzolans in blended concrete improves the strength of concrete due to synergic effects.…”
Section: Slump Testsupporting
confidence: 65%
“…Chindaprasirt and Rukzon [33] indicated that the incorporation of FP caused the carbonation depth to decrease compared to cases in which coarse particles were used. They demonstrated that the amount of SP required was reduced by FP and that the mortar strength was improved compared to coarser POFA concrete.…”
Section: Resistance To Carbonationmentioning
confidence: 98%
“…Chindaprasirt and Rukzon [33] reported that the total porosity of mixed cement pastes can be increased compared to that of OPC paste when POFA is employed. When these pastes were subjected to 50% relative humidity (RH) and 5% CO 2 for 28 d, the pore voids were filled, and attacks on C-S-H were likely to occur.…”
Section: Resistance To Carbonationmentioning
confidence: 98%
“…In contrast, other authors have reported an increase in the specific surface area after carbonation; e.g., Da Silva et al (2002) and Chindaprasirt (2009) conducted mercury porosimetry studies on concrete, Arandigoyen et al (2006) investigated nitrogen adsorption on cement pastes that consisted of a mixture of cement and lime and Kim et al (1995) examined the carbonation of portlandite and C-S-H.…”
Section: Introductionmentioning
confidence: 95%